Effect of prefiring temperature on the texture and optical property of Bi4Ti3O12/MgO(100) prepared by using a metal naphthenate precursor - Hwangbo, Seung; Hwang, Kyu-Seog; Kim, Jin-Tae (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The effect of prefiring temperature on the crystal structure and optical property of the Bi4Ti3O12 films on MgO substrates by using a metal naphthenate precursor was investigated. As-deposited films were prefired at 300 °C, 400 °C and 500 °C for 10 min, followed by annealing at 750 °C for 30 min. According to the pole-figure analysis, texture of the annealed films was found to depend on prefiring temperature. Transmittance and the variation of band gap with prefiring temperature were studied.
Optica Applicata, Vol. 38, 2008, nr 4, s. 635-641
Keywords: optyka; prefiring temperature; metal naphthenate; texture; optical property